2019
DOI: 10.1103/physrevb.100.094426
|View full text |Cite
|
Sign up to set email alerts
|

Topology analysis for anomalous Hall effect in the noncollinear antiferromagnetic states of Mn3AN (A=Ni, Cu,

Abstract: We investigate topological features of electronic structures which produce large anomalous Hall effect in the non-collinear antiferromagnetic metallic states of anti-perovskite manganese nitrides by first-principles calculations. We first predict the stable magnetic structures of these compounds to be non-collinear antiferromagnetic structures characterized by either T1g or T2g irreducible representation by evaluating the total energy for all of the magnetic structures classified according to the symmetry and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 38 publications
4
30
2
Order By: Relevance
“…Our previous studies demonstrated that the electrical switching of H ex is realized in antiperovskite nitride AFM-Mn 3 GaN/FM-Co 3 FeN (001) bilayers with a current density of 1 × 10 6 A/cm 2 , which is two orders of magnitude smaller than typical FM cases 39 . Towards further understanding, we introduce that the noncollinear AFM antiperovskite manganese nitride Mn 3 AN may be a good platform because the AFM magnetic properties, such as the Mn local moment and AFM spin structure (Γ 4g and Γ 5g ), depend on the A atom [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that the electrical switching of H ex is realized in antiperovskite nitride AFM-Mn 3 GaN/FM-Co 3 FeN (001) bilayers with a current density of 1 × 10 6 A/cm 2 , which is two orders of magnitude smaller than typical FM cases 39 . Towards further understanding, we introduce that the noncollinear AFM antiperovskite manganese nitride Mn 3 AN may be a good platform because the AFM magnetic properties, such as the Mn local moment and AFM spin structure (Γ 4g and Γ 5g ), depend on the A atom [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the AHE has been predicted theoretically and confirmed experimentally in Mn based antiperovskite nitrides with the Γ 4g AFM order [29,[57][58][59][60]. Due to the AHC being odd with respect to the time reversal symmetry operation, reversal of the AFM order in the Γ 4g type antiperovskites is expected to change sign of the AHE (Fig.…”
mentioning
confidence: 88%
“…), the Mn atoms form a kagome lattice in the (111) plane. The noncollinear AFM Mn 3 AN with a nonzero Berry curvature has been predicted to exhibit a large anomalous Hall effect (AHE) and an anomalous Nernst effect even with a quite small canted magnetization of the order of 0.001-0.01 µ B per atom [15][16][17]. The AHE has been established in Mn 3 Ni 1−x Cu x N films [18,19], strained Mn 3 NiN films [20], and strained Mn 3 SnN films [21].…”
Section: Introductionmentioning
confidence: 97%